Claiming the Basileia ton Rhomaion: A Latin Imperial Dynasty in Byzantium (1204-1261). (October 2017) - Van Tricht, Filip
In April 1204, the army of the Fourth Crusade captured Constantinople. For the leading princes, it was self-evident that they would install an imperator of their own in the Queen of Cities. Their choice fell on Baldwin IX/VI, count of Flanders/Hainault. In this contribution, we aim to analyse how Baldwin and his successors saw their emperorship, and how they and their empire were seen by others in Byzantium and the West. The current historiographical term, 'Latin Empire of Constantinople', reflects the prevailing view that an entirely new political construct had been set up replacing the former Byzantine Empire. However, contemporaries, both the emperors themselves as well as outsiders, consistently referred to the empire using both Latin and Greek terms that, prior to 1204, had been commonly employed to refer to the Byzantine Empire. Yet eastern and western conceptions of the nature of the empire before 1204 differed greatly: it was 'Greek' in Latin eyes, 'Roman' in Byzantine eyes. The Constantinopolitan imperial crown having been placed on his head, Baldwin became heir to these conflicting traditions. Moreover, rival imperial claims soon arose within the Byzantine space in neighbouring Byzantine successor states. In the face of these challenges, the Latin emperors strove to formulate a political ideology legitimising their claim to imperial rule. We will argue that in essence the successive Latin emperors adopted, up to a point, the key tenets of Byzantine imperial theory (Roman character, universalism, emperors as vicars of Christ and autocracy). Their western background and their different relationship with the West led to certain changes, but whether these should be seen as fundamentally un-Byzantine is not self-evident. Conversely, the presence of the now Latin rulers on the Constantinopolitan throne also led to changes in the western perception of the eastern empire.